Untapped bacterial diversity and metabolic potential within Unkeshwar hot springs, India - Mehetre, Gajanan T. (Archives of Microbiology, 2018)
Hot springs support diverse and interesting groups of microorganisms adapted to extreme conditions and gaining attention in biotechnological applications. However, due to limitations of cultivation methods, a majority of such extremophiles remain uncultivated and unexplored. The advent of multiple cultivation conditions and specialized culture media could possibly aid to access the unexplored microbial portion of hot springs. In the present study, different media and isolation strategies were applied to isolate hitherto unexplored bacterial taxa in the water samples collected from Unkeshwar hot springs, India. Molecular, phylogenetic and predictive functional characterization of the isolated bacterial population was done using 16S rRNA sequencing coupled with Tax4Fun tools. Furthermore, representative isolates were screened for important enzymes (cellulase, xylanase, amylase, and protease) and heavy metal tolerance (chromium, arsenic) properties. A total of 454 bacterial isolates obtained were mapped into 57 unique bacterial genera and 4 different bacterial phyla. Interestingly, 37 genera not previously isolated from Indian hot springs, were isolated for the first time in the present study. However, most of these genera (23 out of 37) were reported only in metagenomics studies from Indian and global hot springs. Furthermore, around 14 genera not previously cultivated and not detected in metagenomics studies of hot springs are documented here. The metabolic potential was ascertained by determining the abundance of specific genes using in silico based Tax4Fun tool, which identified around 315 metabolic pathways for metabolism of carbohydrates, synthesis of secondary metabolites and degradation of xenobiotic compounds. Bioprospection study revealed that 33 and 25 bacterial genera were positive for enzyme production and resistance to the heavy metals, respectively. The present study revealed the advantages of cultivation methods using a comprehensive multiple isolation approach for exploring untapped and unique bacterial diversity, and also utilities for various biotechnological and environmental applications.
Keywords: Bacterial diversity; Bioprospecting; Cultivation; Heavy metals; Untapped

Antimicrobial profiling of coral reef and sponge associated bacteria from southeast coast of India - Rajasabapathy, Raju; Ghadi, Sanjeev C.; Manikandan, Balakrishnan; Mohandass, Chellandi; Surendran, Akhila; Dastager, Syed G.; Meena, Ram M.; James, Rathinam Arthur (2020)
Culturable bacteria associated with marine sponges and coral mucus (collected from Gulf of Mannar and Palk Bay) were screened for their prospective antimicrobial compounds against 9 bacterial pathogens (Bacillus megaterium, B. cereus, Salmonella typhimurium, Staphylococcus aureus, Proteus vulgaris, Klebsillla pneumoniae, Escherichia coli, Pseudomonas aeruginosa and Acinetobacter baumannii) and a fungal pathogen (Candida albicans). Of the 263 bacterial isolates obtained during this study, 52 isolates displayed antimicrobial activity against one or more pathogens. 16S rRNA gene sequencing revealed that these 52 strains affiliated to 14 genera from three phyla Proteobacteria, Firmicutes and Actinobacteria. Sponge associated bacterial strains F-04, 1-23, 1-33 and G-03 inhibited the growth of all the bacterial pathogens tested in this study and significantly the former 2 strains inhibited the growth of fungal pathogen also. Majority of the potential strains (88.4% out of 52 strains) inhibited the growth of Bacillus cereus. Interestingly, an actinomycete strain F-04 (isolated from sponge Orina sagittaria) inhibited the growth of methicillin resistant Staphylococcus aureus. In total, 10 volatile organic compounds were determined from the ethyl acetate and hexane extract of the strain F-04 using GC-MS. Overall, marine bacteria isolated during this study demonstrate the potential for the development of broad spectrum antibiotics.
Keywords: Anti-MRSA; Antimicrobial activity; Bacterial diversity; Coral reef; Sponge

Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Seasonal dynamics and tree foliar habit drive the rhizobacterial diversity in congeneric Ficus species from Northern Western Ghats, India - Salunkhe, Vaishnavi H.; Kunte, Pooja S.; Paul, Dhiraj; Kasodekar, Amol K.; Kadoo, Narendra Y. (Rhizosphere, 2023)
Tree species, annual climatic cycle, and geochemical properties influence the tree rhizospheric microbiome. However, its understanding in the moist deciduous forest of Northern Western Ghats (NWG), India, is limited. Moreover, the effects of foliar habits of trees and seasonal variations on rhizobacterial communities across congeneric tree species are unexplored. Hence, we employed high throughput 16 S rRNA gene sequencing to examine the effects of foliar habits of congeneric tree species and seasonal influences on the rhizobacterial community. For this study, rhizospheric soil from Ficus arnottiana (deciduous) and Ficus talboti (evergreen) trees from NWG, India, was collected during three seasons (summer, monsoon, and winter) and subjected to high throughput sequencing. A total of 3031 amplicon sequence variants (ASV) were observed, of which 1257 and 1181 ASV were unique to F. arnottiana and F. talboti, respectively, and 593 ASV were common to both species. The phyla Actinobacteria, Proteobacteria, Acidobacteria, and Chloroflexi were ubiquitous and contributed >90% to the rhizobacterial community. Some bacterial phyla were exclusively associated with either of the tree species and seasons. Different bacterial phyla performed similar functions in different seasons, indicating their functional redundancy and emphasizing their resilience and adaptability across seasons. It was observed that seasonal dynamics mainly drove the rhizobacterial diversity; however, it was also influenced by the foliar habits of the trees and geochemical properties. The study enhances the understanding of congeneric tree microbiomes and offers valuable insights into their potential applications through microbiome engineering.
Keywords: Amplicon variants; Bacterial diversity; Ficus arnottiana; Ficus talboti; Rhizosphere